The Intro Course: A Pedagogical Toolkit - Thorpe, Jocelyn; Boon, Sonja; Bednar, Lisa; Bonifacio, Glenda Tibe; Hobbs, Marg; Hurst, Rachel; Johnston, Krista; Latimer, Heather; Leung, Helen Hok-Sze; Lovrod, Marie; Rice, Carla; Salah, Trish; et al. (Atlantis, 2016)
This article offers ideas and strategies for teaching introductory-level courses in Gender and Women’s Studies by providing the responses of eleven experienced educators who were asked two questions: What main theme or idea do you hope students will learn in the introductory class you teach? And what practical strategies do you use in the classroom to achieve that learning objective?